Tradicija v sodobnosti Janče - zeleni prag Ljubljane - Poljak Istenič, Saša (Ethnologica - Dissertationes, 2013)
The book ('Tradition in the Contemporary World. Janče: the Green Threshold of Ljubljana') deals with dimensions of tradition in modernity, as reflected in the half-urbanized environment on the northeastern outskirts of Ljubljana - at Janče with its surroundings. The author analyzes the concept of tradition, which is one of the core in ethnology and folklore studies, and presents its concretizations in the ethnographic field, especially its role in local festivals. She mainly focuses on peasant work and its ritual dimensions as well as on other types of heritage/tradition of rural environment. Heritage is not only positively valued by local inhabitants, but also represented in the idealistic form, thus creating rural idyll, attractive for tourists. Having a special value, it has become the means of invoking and preserving identifications with certain communities and the area itself, and is at the same time also used as an argument in general and sustainable development of the area.